2021
DOI: 10.3171/2020.6.jns201548
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus radiosurgery for facial nerve schwannoma: a systematic review and meta-analysis of facial nerve function, postoperative complications, and progression

Abstract: OBJECTIVEIntracranial facial nerve schwannomas (FNS) requiring treatment are frequently recommended for surgery or stereotactic radiosurgery (SRS). The objective of this study was to compare facial nerve function outcomes between these two interventions for FNS via a systematic review and meta-analysis.METHODSA search of the Ovid EMBASE, PubMed, SCOPUS, and Cochrane databases from inception to July 2019 was conducted following PRISMA guidelines. Articles were screened against prespecified criteria. Facial nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Our cohort of patients receiving surgical salvage therapy was small and therefore no variable examined was significant in predicting poor outcomes (CSF leak, worsening of facial nerve grade, and completeness of resection). Salvage surgical treatment after SRS in our cohort was notable for higher rates of postoperative complications, for example, 17% with postoperative CSF leak requiring return to the operating room and facial nerve function worse than preoperative function in 65%, compared to primary surgery reported in the literature (64–66). The strategy toward subtotal resection following SRS noncontrol is generally considered a good strategy for facial nerve outcomes, but tumors that continue to grow after SRS are likely more biologically aggressive and are likely at higher risk for continued growth after subtotal resection (67).…”
Section: Discussionmentioning
confidence: 74%
“…Our cohort of patients receiving surgical salvage therapy was small and therefore no variable examined was significant in predicting poor outcomes (CSF leak, worsening of facial nerve grade, and completeness of resection). Salvage surgical treatment after SRS in our cohort was notable for higher rates of postoperative complications, for example, 17% with postoperative CSF leak requiring return to the operating room and facial nerve function worse than preoperative function in 65%, compared to primary surgery reported in the literature (64–66). The strategy toward subtotal resection following SRS noncontrol is generally considered a good strategy for facial nerve outcomes, but tumors that continue to grow after SRS are likely more biologically aggressive and are likely at higher risk for continued growth after subtotal resection (67).…”
Section: Discussionmentioning
confidence: 74%
“…Preoperative facial nerve function is also an important determinant in decision-making in FNS, hence surgeons recommend observation to patients with minimal degradation in facial function; SRS for moderate reduction in facial function; and surgery with or without grafting for poor facial nerve function (HB IV or worse) or for signi cant mass effect [2,12,13]. Studies have suggested that with a treatment goal of preventing the tumor growth while preserving function of facial nerve in FNS, surgery poses a higher risk of facial palsy compared to SRS for facial nerve function [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the efficacy and safety of radiotherapy [13,14]. A previous study reported that the treatment-induced exacerbation of facial nerve paralysis significantly increased with surgery, whereas there was no significant difference in local control rates between surgery and radiotherapy for intracranial facial nerve schwannomas [15]. Regarding local tumor control rate, preservation of facial nerves, and hearing ability, hypofractionated stereotactic radiosurgery is reported to be more beneficial in radiosurgery [16 ▪▪ ].…”
Section: Facial Nerve Schwannomamentioning
confidence: 99%